Impact of perinatal administration of probiotics on immune cell composition in neonatal mice - Rühle, Jessica; Schwarz, Julian; Dietz-Ziegler, Stefanie; Rückle, Xenia; Schoppmeier, Ulrich; Lajqi, Trim; Poets, Christian F.; Gille, Christian; Köstlin-Gille, Natascha (Pediatric research, 2024)
Newborns and especially preterm infants are much more susceptible to infections than adults. The pathogens causing infections in newborns are often detectable in the intestinal flora of affected children even before disease onset. Therefore, it seems reasonable to prevent dysbiosis in newborns and preterm infants. An approach followed in many neonatal intensive care units (NICUs) is to prevent infections in preterm infants with probiotics however their mechanisms of action of probiotics are incompletely understood. Here, we investigated the effect of perinatal probiotic exposure on immune cells in newborn mice.
Gesehen am 22.10.2024